Copper level and metallothionein-like Cu-binding protein in cultured skin fibroblasts from patients with Menkes' disease and Wilson's disease - Sato, M; Hayashi, A; Ito, H; Tojo, M; Arima, M (No To Shinkei, 1984)
Copper concentration, intracellular copper distribution, and inducibility of metallothionein-like metal-binding protein (MLP) by copper or cadmium addition to culture medium were compared among three types of skin fibroblasts derived from patients with Menkes' disease and Wilson's disease, both exhibiting genetic defects of copper metabolism, and from normal subjects (control). Skin fibroblasts were cultivated in Dulbecco's modified Eagle's medium supplemented with 10% fetal calf serum and antibiotics in 5% CO2 at 37 degrees C. Cells were harvested with rubber-policeman, washed twice with phosphate-buffered saline, pH 7.2, suspended in deionized water, and homogenized. The homogenate from each cell type was used to determine the concentration of copper by atomic absorption spectrophotometry employing graphite-rod atomizer after lyophilization, ashing in HNO3, and coprecipitation with zirconium. Intracellular copper concentration was elevated in Menkes' cells (420 ng Cu/mg of protein) and Wilson's cells (217 ng Cu/mg of protein) than in control cells (90.0 ng Cu/mg of protein), although one of four Wilson's strains showed normal copper level (70.5 ng Cu/mg of protein). Cytosol copper concentration was 5.8-fold higher in Menkes' cells but only 1.3-fold in Wilson's cells than in control cells, and cytosol copper accounted for only 35% of total intracellular copper in Wilson's cells as compared with 68% and 52% in Menkes' and control cells, respectively. These suggest that accumulated copper in each cell type is differently distributed within cells; in Menkes' cells exclusively into cytosol, but in Wilson's cells into particulates rather than cytosol. Elution profiles from Sephadex G-75 columns indicated that most of copper had bound to MLP in Menkes' cells, though no Cu-MLP was detectable in Wilson's or control cells under these experimental conditions.(ABSTRACT TRUNCATED AT 250 WORDS)